2017
DOI: 10.3382/ps/pex124
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage use to control Salmonella biofilm on surfaces present in chicken slaughterhouses

Abstract: Foodborne diseases represent a major risk to public health worldwide. Pathogenic bacteria can live in the form of biofilm within the food industry, providing a permanent source of contamination. The aim of this study was to evaluate the influence of the types of adhesion surfaces on Salmonella biofilm formation at eight different times, and analyze the action time of a bacteriophage pool on established biofilms. Most of the samples used were classified as weak biofilm producers, with serovars Enteritidis and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…Conversely, our Salmonella Typhimurium isolates had the highest overall attachment capacity in this study. Studies of Salmonella Heidelberg have generally found it to be an average biofilm former (56,57). In contrast, our data indicated that all Salmonella Heidelberg isolates except R1-0001 and R1-0005 were weak or nonattaching biofilm formers, using the categories and conditions defined by Stepanović et al (24 h of attachment at 35°C; we tested the isolates at 37°C; data not shown) (16).…”
Section: Discussioncontrasting
confidence: 50%
“…Conversely, our Salmonella Typhimurium isolates had the highest overall attachment capacity in this study. Studies of Salmonella Heidelberg have generally found it to be an average biofilm former (56,57). In contrast, our data indicated that all Salmonella Heidelberg isolates except R1-0001 and R1-0005 were weak or nonattaching biofilm formers, using the categories and conditions defined by Stepanović et al (24 h of attachment at 35°C; we tested the isolates at 37°C; data not shown) (16).…”
Section: Discussioncontrasting
confidence: 50%
“…Another concern is the efficacy of phages in tackling intracellular pathogens. Nonetheless, it has been reported that phages were successful in preventing salmonellosis (Lazriev et al 1986) and Salmonella biofilm production (Garcia et al 2017). The side effects of phage therapy in the long run remain unknown.…”
Section: Disadvantages Of Phage Therapymentioning
confidence: 99%
“…compared to polyvinyl chloride surface (PVC). Moreover, S. Enteritidis and S. Heidelberg had stronger biofilm-forming ability than other serovars tested [68].…”
Section: Use Of Bacteriophages As Disinfectantsmentioning
confidence: 81%